STUDENT LEARNING ACHIEVEMENTS REVIEWED FROM LEARNING FACILITIES, PEER ENVIRONMENT, MOTIVATION, AND DISCIPLINE (Study at SMP Batik Surakarta) - Destomo, Deny; Istiatin, Istiatin; Sudarwati, Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The research aims to determine the influence of the following variables; facilities of the study, peer environment, motivation, and discipline toward student’s achievement in SMP Batik Surakarta both simultaneously and partially. The researcher uses a descriptive quantitative method. The research populations are students in IXA and IXB (excellent class) of SMP Batik Surakarta, consisting of 61 students. The sampling technique uses cencus technique which covers 61 respondents. The researcher uses a questionaire to collect the data. While data analyzing technique uses statistical analysis, multiple linear regression test, F test, T-test, and coefficient determination. The research finding shows that facilities of the study, peer environment, motivation, and discipline give significant influence toward students achievement 72,8%. In comparison, 27,2% is influenced by other variables such as learning interest, teacher’s competence, etc. Keyword: student’s achievement, facilities of the study, motivation, and discipline.